Forgotten continent the battle for Latin America?s soul - Reid, Michael (Blackstone, 2011)
Latin America has often been condemned to failure. Neither poor enough to evoke Africa?s moral crusade, nor as explosively booming as India and China, it has largely been overlooked by the West. Yet this vast continent, home to half a billion people, the world?s largest reserves of arable land, and 8.5 percent of global oil, is busily transforming its political and economic landscape.
Keywords: Democracy -Latin America -History.